2017
DOI: 10.1007/s13353-017-0404-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of KLOTHO and SFRP1 promoter methylation in head and neck squamous cell carcinoma

Abstract: Hypermethylation in the CpG island promoter regions of tumor suppressors is known to play a significant role in the development of HNSCC and the detection of which can aid the classification and prognosis of HNSCC. This study aims to profile the methylation patterns in a panel of key genes including CDKN2A, CDKN2B, KLOTHO (KL), RASSF1A, RARB, SLIT2, and SFRP1, in a group of HNSCC samples from Saudi Arabia. The extent of methylation in these genes is determined using the MethyLight assay and correlated with kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In case of several head and neck cancer-related genes (such as SST, CXXC4, DACT2, RASSF1A, MGMT1, SFRP1, GNG7), altered methylation patterns were identified (Hartmann et al 2012;Misawa et al 2015;Koutsimpelas et al 2012;Paluszczak et al 2017;Alsofyani et al 2017). However, most significant disadvantage of those studies was employment of tissue specimens as primary material, which limits diagnostic value of these findings due to high invasiveness during sample collection and laborious microdissection procedures allowing to select cancer cells from the stroma of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In case of several head and neck cancer-related genes (such as SST, CXXC4, DACT2, RASSF1A, MGMT1, SFRP1, GNG7), altered methylation patterns were identified (Hartmann et al 2012;Misawa et al 2015;Koutsimpelas et al 2012;Paluszczak et al 2017;Alsofyani et al 2017). However, most significant disadvantage of those studies was employment of tissue specimens as primary material, which limits diagnostic value of these findings due to high invasiveness during sample collection and laborious microdissection procedures allowing to select cancer cells from the stroma of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical Genetics (2020) 58:213-244 and meta-analyses (Sanchez-Cespedes et al 2000;Don et al 2014;Choudhury and Ghosh 2015;Sushma et al 2016;Dvojakovska et al 2018;Alsofyani et al 2017;Veeramachaneni et al 2019). Allameh et al (2018) reported a higher methylation level of its promoter in OSCC patients compared to a control group, and hypermethylation was associated with lower expression of that gene in tumor samples.…”
mentioning
confidence: 99%
“…Compared to normal tissues, tumor tissues usually have a dramatically reduced KL expression 10,19,25. Previous studies have reported reduced KL protein levels in ESCC and OSCC 15,17. Furthermore, decreased KL protein levels usually parallel with increased DNA methylation in its promoter region and are associated with poor prognosis for a variety of cancers, such as hepatocellular cancer,24 gastric cancer26 and ESCC 15.…”
Section: Discussionmentioning
confidence: 99%
“…KL promoter hypermethylation has been reported to silence its expression and consequently leads to the loss of its tumor suppressive function 9. In fact, KL promoter hypermethylation has been found in malignancies such as HNSCC,17 breast cancer,9 colorectal cancer18 and cervical cancer 19. These findings raise the surge of evaluating KL expression and its DNA methylation as potential prognosticators in HNSCC.…”
Section: Introductionmentioning
confidence: 98%